Statistical study of the growth kinetics and lipid content of microalgae cultivated in brackish media, using wastewater as a source of nutrients for bioenergetic purposes (Research, Society and Development, 2022)
The present work aimed to prove, statistically, the influence of the concentration of nutrients from fossil waters on the growth kinetics and intracellular lipid accumulation in microalgae. The species Chlorella sp., Scenedesmus acuminatus, Nannochloropsis sp., Monoraphidium contortum and Pediastrum tetras were studied, which were isolated from the semiarid region of the Brazilian northeast and cultivated in a mixture composed of brackish groundwater and effluent from septic tanks. From the crops, the kinetic parameters, dry biomass production and lipid content were analyzed, using the experimental planning for one factor as a tool, with the concentration of nutrients as an independent variable. The maximum growth velocity (μmax), generation time (tg), as well as the lipid content were the studied response variables. The results showed that the species with the greatest accumulation of lipids were Chlorella sp., with a lipid content of 81.20%, and Nannochloropsis sp. with 73.68%, being the most promising for bioenergetic purposes. Therefore, the concentration of nutrients from fossil effluents combined with the salinity of the medium acted directly on cell growth and lipid content, and such factors can be used as an artifice to enhance lipid production, aiming at the production of biofuels.